Roasted coffee industry in the region of Los Santos, Costa Rica: a local rural conglomerate - Díaz Porras, Rafael (2024)
This paper aims to understand the dynamics of the roasted coffee industry in a coffee-producing region. The activity is studied by using the concept of local development since the coffee-growing dynamics of the Los Santos region in Costa Rica take place in a conglomerate space. However, the case presents features in which there is a crossover of both horizontal dimensions, coming from the local social mechanism, as well as vertical dimensions, typical of value chains. A three-trend process is observed: the productive trajectory of the coffee activity, linked to the socioeconomic trajectory and the local-organizational trajectory. In conclusion, the development of the roasted coffee industry in Los Santos cannot be understood without observing its context: local development with the capacity to respond to global changes; emergence of micro-mills; and the particular characteristics of a maturing conglomerate, stemming from the spontaneity of the process.